Dampak Struktur Modal dan Profitabilitas terhadap Nilai Perusahaan pada Sub Sektor Perkebunan yang Go Publik di Bursa Efek Indonesia - Gaffar, Gaffar; Ariawan, Ariawan (Journal of Technopreneurship on Economics and Business Review, 2021)
This study aims to determine the effect of capital structure (X1), profitability (X2) simultaneously and partially on firm value in plantation sub-sector companies that go public on the Indonesia Stock Exchange. This study uses a quantitative approach. Determining the sample of companies using purposive sampling technique by considering companies that are listed and no listed on the Indonesia Stock Exchange and have financial statements from 2015-2019, so the total sample is 7 companies in the plantation sub-sector. Sources data of research are from audited company annual reports and from the Indonesia Stock Exchange (www.idx.co.id) and ICMD (Indonesia Capital Market Directory). The result of the study shows that the capital structure and profitability simultaneously have a significant effect on firm value. Capital structure partially has no significant effect on firm value in plantation sub-sector companies listed on the Indonesia Stock Exchange.